Pet care application - Yew, Zhi Hao (2024)
The major purpose of this project is to create a full Pet Care application designed specifically for Malaysian pet owners, incorporating services such as pet transportation, medical booking, e-commerce for pet items, and a Tamagotchi-style game. This project is an academic endeavor designed to improve competence in mobile application development, user-centric design, and new technology solutions for the pet care business. Many businesses turned to online platforms in response to the COVID-19 outbreak, but Malaysian pet owners confront problems such as public transport constraints, cultural sensitivities, and limited access to necessary services. These issues, combined with an increasing number of pet owners, highlight the necessity for a specialized application that offers convenient solutions. The Pet Care program solves these concerns by providing a dedicated platform for users to book pet taxis, plan medical visits, purchase pet supplies, and participate in a virtual pet care game that teaches users about pet ownership responsibilities. The program is built utilizing the Agile technique, which emphasizes iterative development, continual feedback, and adaptability to changing requirements. Agile enables regular updates and communication with end-users, ensuring that the application grows to suit user needs throughout the development cycle. Key features include pet taxi services with verified drivers, a veterinary booking system that lowers wait times, and an e-commerce platform with a diverse assortment of pet products. Furthermore, the Tamagotchi-style game offers an interesting educational experience by allowing users to practice taking care of a virtual pet. To provide a consistent and user-friendly experience, the Agile strategy includes intensive user testing and regular feedback loops. By bringing together drivers, doctors, and merchants, the project seeks to not only provide value to pet owners but also to create new job possibilities in the pet care business, thereby benefiting the local economy.